3,5-Dibromo-2-[2,5-dibutoxy-4-(3,5-dibromothiophen2-yl)phenyl]thiophene - Teh, Chin Hoong; Daik, Rusli; Mat Salleh, Muhammad; Mohamed Tahir, Mohamed Ibrahim; Kassim, Mohammad (International Union of Crystallography, 2011)
The title molecule, C22H22Br4O2S2, is centrosymmetric with an inversion centre located at the centre of the benzene ring. The 3,5-dibromothiophene groups are twisted relative to the benzene ring, making a dihedral angle of 41.43 (9)°.